Enhancing Public Private Partnership for Effective Management of Higher Education Institution Resources - Alao, Aderonke Olubukola (International Journal of Educational Management, 2021)
The higher education institutions include Universities, Polytechnics and Colleges of Education among others., The contributions of the output of these institutions to the development a nation are numerous. However, inadequate financial material and human resources in Nigeria tertiary institutions have constantly led to incessant strikes and dwindling quality of education offered. The public- private partnership in the government owned tertiary institutions has positively impacted the state of affairs in the delivery of educational services. Nevertheless, to further improve and sustain the availability and management of resources for learning, the problems encountered in public private collaboration such as poor infrastructure, corruption, political influence should be examined while favourable environments should be created by government and institutional administrators to encourage more participation of prospective private investors to foster a qualitative sustainable higher education system.